The effect of the dynamic splitting of the conductivity state in homogeneous electric field - Suprun, A.D.; Shmeleva, L.V. (Functional Materials, 2018)
The features of a completely homogeneous external electrostatic field effect on the properties of a quasiparticle of the electron type injected into the conduction band of a semiconductor or dielectric are considered. As applied to this case (completely homogeneous external field), the equations obtained earlier are analyzed, which provide a consistent quantum (basic) and classical (in terms of quasiparticles) descriptions. It is shown that these equations reflect regularities that do not allow the "direct" application of the external field both in the basic (quantum) and in the effective (in terms of quasiparticles) descriptions. These regularities and the corresponding equations are one of the possible causes for the experimentally observed anomalous splitting of the conductivity state in strong fields. In the article this splitting was called a dynamic splitting. A satisfactory agreement with the experiment was obtained.